Drug screening for ischemic stroke using larvae and adult zebrafish model: a review - Ni Made Dwi Mara Widyani Nayaka; I Ketut Adnyana; Kusnandar Anggadiredja; Indra Wibowo (Laboratory Animal Research)
Abstract Ischemic stroke (IS) is the most recorded case of stroke that is caused by decreased blood flow to the brain. Nowadays, therapeutical agents for IS are limited and they have not shown maximum clinical results. Therefore, the exploration of new candidates for IS treatment continues to be done. Zebrafish as one of the animal models has its advantages and currently is being developed to be incorporated into the drug discovery pipeline of IS. This review explores the latest applications of the zebrafish model in screening potential therapeutic agents for IS. Key factors related to the experimental design such as developmental stage and strain, routes of drug administration, induction methods, and experimental parameters are also elaborated. Finally, this review offers future recommendations for the use of zebrafish in the pre-clinical study of IS. This review is beneficial as a reference for establishing drug screening protocols using the zebrafish IS model.